Prolonged conflict in Mancani Residen, Palopo City Johan Galtung's peace and conflict studies - Saifur Rahman; Intan Soliha Ibrahim; Wahyuni Husain; Muh. Zulfadli Amin (IanKendari, 2023)
This study examines the phenomenon of protracted conflict that occurred in the Mancani resident, Polapo City by involving two community groups, namely the Batu and Uri community groups. This research answers the root causes of conflict, forms of violence, and forms of peace using Johan Galtung's perspective. This research is qualitative research with a phenomenological and historical approach. The study found that the conflict's root originated from youth but has now extended to impact children and parents, primarily driven by social pathologies such as drinking behavior, sensitivity, and group discrimination. Structural, direct, and cultural violence is evident in Mancani Resident, with these forms influencing each other in a series of conflict events. Peace efforts, initiated by the local government and community leaders, encompass both negative and positive peace. While negative peace, focusing on measures like weapons seizure, is commonly used for conflict resolution, the study recommends prioritizing and maximizing the implementation of positive peace for its long-lasting impact. The urgency of this study is underscored by the revelation of a prolonged conflict in Mancani, Polapo City, involving the Batu and Uri community groups. The pressing need for immediate intervention is underscored by the fact that the conflict, which initially originated from negative youth behavior, has now extended its impact to affect both children and parents. This highlights the urgency to address the underlying social pathologies contributing to the escalation of the conflict.